High-performance and durable cathode catalyst layer with hydrophobic C@PTFE particles for low-Pt loading membrane assembly electrode of PEMFC - Wang, Meng; Chen, Ming; Yang, Zhaoyi; Liu, Guicheng; Lee, Joong Kee; Yang, Woochul; Wang, Xindong (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This paper mainly focuses on the optimization and design of cathode catalyst layer structure for low-Pt loading membrane assembly electrode. When Pt loading at cathode increased from 0.025 mg cm(-2) to 0.4 mg cm(-2), the apparent current density of electrode increases gradually, while the electrochemical active surface area (ECSA) and the utilization rate of catalyst show a downward trend. As Pt loading at cathode keeps at 0.1 mg cm(-2), commercial Vulcan XC-72 carbon are doped into the conventional Pt/C catalyst layer to improve the utilization rate of the catalyst. The results show that the optimum doping carbon content leads to 2 times increase of the thickness of the cathode catalyst layer, and achieves a 32.93% increase of ECSA and better durability than that of conventional catalyst layer. Meanwhile, gas transport in the catalyst layer becomes more difficult with the increase of the amount of doping carbon. Based on this, a more stable Vulcan XC-72@PTFE particles are prepared and selected to construct internal gas transport channels under the same carbon content. The surface contact angle of the catalyst layer is obviously increased to 118.4 degrees. The hydrophobicity of the cathode catalyst layer is enhanced, and the oxygen gain voltage is significantly reduced. The peak power density of PEMFC reaches 539 mW cm(-2), which is 30.57% higher than that of one with a conventional catalyst layer structure. Therefore, this work provides a good way for the preparation of high-performance and durable cathode catalyst layer for low-Pt loading membrane assembly electrode.
Keywords: FUEL-CELLS; METHANOL; POLYTETRAFLUOROETHYLENE; OPTIMIZATION; PARAMETERS; ANODE